Cities, climate change and public health : building human resilience to climate change at the local level - Kim, Ella Jisun (Climate change (Anthem Press), 2020)
This book examines how cities can use a public health frame of climate change to boost people's understanding of and concern about climate change and increase policy support for climate adaptation efforts at the local level. It also presents new tools for cities to enhance awareness of and facilitate prioritization of climate risk management choices.